The existence of women in Islam studying the film Nyai Ahmad Dahlan - Anggraini Jamilatun; Triska Candra Sari; Mhd Lailan Arqam (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
In Indonesian society, household matters are usually handled by women. To this day, the patriarchal culture still persists. In a patriarchal culture, women are required to possess three skills: macak (dressing up), masak (cooking), and manak (giving birth). A woman's success is measured by her ability to master these three skills; failure to do so results in her being considered worthless within a family and society. However, Islam highly regards women and does not differentiate between men and women except in terms of piety and natural disposition. Siti Walidah fought for this situation, emphasizing that women should reclaim their rights, particularly in education. This study aims to analyze the existence of women in Islam by examining the film 'Nyai Ahmad Dahlan,' which portrays Siti Walidah as a heroine of emancipation in Islamic education. The research uses a descriptive qualitative method and a literature review, drawing data from journals, books, and websites. This literature review concludes that Siti Walidah spread Islam by advocating for women's rights. Throughout her life, Siti Walidah made numerous contributions, such as founding the 'Sopo Tresno' study group, which later became 'Aisyiyah, teaching literacy, and providing job opportunities for women. All these efforts were made by Siti Walidah to ensure that women have the same opportunities as men, thereby advancing the nation.